The Evaluation and Manipulation of Different Kits for Isolation of High-quality RNA from Frozen Blood - Dalkilic, S.; Dalkilic, L. K.; Saleh, K. K.; Mulayim, S.; Hamarashid, B. R.; Kirbag, S.; Kaplan, M. (Springer Int Publ Ag, 2021)
Due to degradation and limited quantities, one of the restrictions of molecular study is the inability to obtain total RNA extraction from frozen blood, while high-quality RNA is required for complementary DNA (cDNA) synthesis and gene expression analysis. To achieve optimal RNA extraction from frozen blood, the performance of three commercial RNA isolation kits, NucleoSpin RNA Blood kit, GENEzol reagent kit, and GeneJET Blood RNA kit, was examined. In addition, the effects of specific manipulation on the two of them (NucleoSpin RNA Blood kit, and GENEzol reagent kit) were evaluated. Agarose gel electrophoresis, Qubit fluorometer, and quantitative real-time PCR (qRT-PCR) were used. The mean yields of total RNA and cycle threshold (Ct) values of gene expression were investigated before manipulation and after manipulation. Three housekeeping genes, DECR1, GAPDH, ACTB, and one target gene P53, were involved. In the results, before manipulation, Ct values of gene expression and yields of RNA showed that the GeneJET, GENEzol, and NucleoSpin were the first, second, and third effective kits for RNA extraction from frozen blood, respectively. On the other hand, after manipulation, RNA yields and Ct values showed significant differences in terms of quantity and quality. Finally, as a result of the manipulation, NucleoSpin was shown to be the best and most powerful kit for isolating RNA from frozen blood. Based on these findings, the ability to obtain high-quality total RNA extraction from frozen blood was one of the major advantages of our modifications.
Keywords: Commercial kits; RNA quantity; RNA quality Gene expression; RT-PCR